Synthesis of ZSM-5 From Natural Zeolite Lampung (ZAL) and Rice Husk by Seeding Method using Microwaves - Ginting, Simparmin Br; Putri, Erisha; Miranda, Thalya; Darni, Yuli; Utami, Herti; Wardono, Herry; Darmansyah, Darmansyah; Rustamaji, Heri (Universitas Negeri Semarang, 2024)
ZSM-5 can be synthesized from Lampung Natural Zeolite (ZAL) and rice husks as a source of additional silica. To speed up the synthesis time, ZSM-5 was synthesized using microwaves. Based on this, the synthesis of ZSM-5 was carried out using microwaves at a temperature of 140 oC with a power of 540 watts with time variations of 10, 15 and 30 minutes with the seeding method as a template replacement of 20%. Amorphous silica with a SiO2 content of 95.324% was extracted from rice husks with a suitable alkali solution. The influence of synthesis time on the formation of ZSM-5 has been carried out. The resulting product was characterized using X-ray Diffraction (XRD), and FTIR (Fourier-Transform-Infrared), Scanning Electron Microscopy (SEM) and BET (Brunaur, Emmet and Teller). The results of the analysis show that the results of the research show that the synthesis of ZSM-5 has been successfully carried out by changing the amorphous phase from natural Lampung zeolite and rice husks into ZSM-5 crystals using microwaves which can shorten the synthesis time 216 - 72 times faster than with heating. conventional, produces high crystallinity, provides small particle sizes with larger surface area, pore volume and pore diameter, and microwave radiation does not damage the Si-O bonds. The best sample was obtained at a synthesis time of 30 minutes with a crystallinity percentage of 96.76% and a specific surface area of 138.616 m2 /g.